Auroral Structure and Dynamics From GOLD. Issue 3 (2nd March 2020) - Michell, R. G.
Abstract: The Global‐scale Observations of the Limb and Disk (GOLD) mission data contain significant quantitative information about the aurora on a global scale. Here we present techniques for quantifying such information, including the temporal development of the structure within the auroral oval using the GOLD images. These techniques are applied to auroral observations in the GOLD data, in particular showing an example of how the longitudinal structure within the aurora varies over the course of six consecutive days with differing levels of geomagnetic activity. A simple model of the solar‐induced airglow is presented that is used to remove the sunlight contamination from the dayside auroral observations. Comparisons to ground‐based auroral imaging are used for the overall auroral context and to make estimates of the proportionality between the intensities of the green line (557.7 nm) emission in the visible and the 135.6 nm emissions in the GOLD data. These observations are consistent with the intensity of the 135.6 nm auroral emission being on the same order as the intensity of the 557.7 nm auroral emission. They were both found to be around 1 kR for a stable auroral arc on a day with low geomagnetic activity (3 November 2018) and around 10 kR for an active auroral display on a day with higher levels of geomagnetic activity (5 November 2018). This could have important implications for making direct comparisons between space‐based ultraviolet auroral imaging and ground‐based visible‐light auroral imaging and the total energy input estimates that are derived from them. Key Points: Longitudinal keograms created over long time series of GOLD dayside images quantify significant auroral structure and development A simple estimate of the solar‐induced airglow is used to remove most of the solar contamination of the sunlit aurora The intensity of the 135.6 nm aurora and the intensity of the 557.7 nm aurora are similar (1 kR for weak aurora and 10 kR for strong aurora)